Levels of Organizational-Pedagogical Conditions of Professional Self-Improvement of the Head of Out-Of-School Educational Establishment (by the Example of the Head of Children’s Sports School) - Kholostenko, Tetyana (Pedagogical Discourse, 2012)
Scientific researches with the aim of identifying possible levels of organizational-pedagogical conditions of professional self-improvementof the head of out-of-school educational establishment (by the example of the head of children’s sports school) are analysed in the article. Four levels (state, municipal, inside school, personal) of organizational-pedagogical conditions, which influence the professional self-education of the head of children’s sports school are identified.